ANALISIS PENERAPAN PENDIDIKAN PANCASILA DALAM MENUMBUHKAN SIKAP MANDIRI SISWA KELAS V SDN 01 BENGKAYANG - Vili Keristina; Kusnanto (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the implementation of Pancasila Education in fostering independent attitudes among fifth-grade students at SDN 01 Bengkayang. A descriptive qualitative method was used with data collected through observation, interviews, and documentation. The results show that Pancasila values are integrated through classroom learning, teacher role modeling, and school habituation activities. Students demonstrated independence through completing assignments, asking questions, and taking responsibility for learning tasks. However, several obstacles were identified, including low learning focus and dependence on others. The study concludes that Pancasila Education plays an important role in fostering students' independence.